PERANAN IKHLAS DALAM PERSPEKTIF AL-QUR’AN - Hasiah, Hasiah (IAIN Padangsidimpuan, 2013)
Not all of the Qur'an can be seen in a clear and definite meaning. However, it requires prudence in thinking and understanding as well as other sincerity which it means sincerity.